Lipoma, the universal tumor: in a rare location - Prajapati, Devendra K.; Mahajan, Salil; Prajapati, Jyoti M. (International Surgery Journal, 2017)
Lipoma is universal and abundantly located benign soft tissue tumor, which is composed of fat cells. These tumors often develop where adipose tissue is predominant. Lipomas are soft to firm/cystic, usually movable, and painless. They grow very slowly, and have rarely found to be cancerous. However, these are rarely localized in the plantar aspect of the foot. Here we find out a large benign tumor located in the planter surface of foot, finally diagnosed by histopathological examination.